Theories of Change: Making Value Explicit - Steve Powell (The Evaluation Center at Western Michigan University, 2019)
Background: This article addresses two problems. The first is the Flexibility Problem: If we are to use a more flexible format for theories of change than for traditional logic models, one in which we can no longer assume that we only value things which are at the end of causal chains, nor that we intervene on all the things at the beginning of causal chains, how then can we show which things we value, and which things we intervene on? The second is the Definition Problem: What is the difference between a theory showing the causal influences within and around a project and, more specifically, a theory of change for the project?   Purpose: To solve the Flexibility Problem and the Definition Problem.   Setting: N/A   Intervention: N/A   Research Design:  N/A   Data Collection and Analysis: N/A   Findings: A definition of "Theory of Change" is introduced, based upon a definition of "Theory" together with two symbols to mark variables we value ("♥", or any suitable alternative symbol) and variables we intervene on ("▶", or any suitable alternative symbol). These two definitions and the two symbols together answer both the Flexibility Problem and the Definition Problem, and have some interesting side-effects as follows. Firstly, they suggest that it is the task of evaluators to model how stakeholders value aspects of a project just as much as it is to model the causal chains within a project. Secondly, evaluators are able to model the fact that stakeholders may value variables which are not at the end of a causal chain, throwing a new light on the debate between results-based and principles-based programming. Thirdly, they provide a way to understand the behaviour of stakeholders and stakeholder groups in terms of their own theories of change - the way they view the world and how they can get what they want - rather than from the traditional behaviourist perspective more familiar to most evaluators.